Correlation between phosphorylated H1 histones and satellite DNAs in Drosophila virilis. - Blumenfeld, M (1978)
Drosophila virilis DNA contains satellites I, II, and III. D. novamexicana DNA contains satellite I. D. virilis H1 histone contains subfractions a, b, c, d, and e; D. novamexicana H1 contains subfractions a, b, and c. Therefore, satellites II and III might be correlated with H1d and H1e. To test the validity of this correlation, the H1 histones of polytene nuclei, which contain less than 1% satellite DNA, were analyzed. Polytene nuclei of D. virilis contain substantially decreased levels of H1c and H1e and marginally decreased levels of H1d. Polytene nuclei of D. novamexicana contain decreased levels of H1c.H1c is correlated with satellite I (common to D. virilis and D. novamexicana); H1e is correlated with satellites II and III; H1d is not correlated with any satellite DNA, because its level is virtually unchanged in polytene cells lacking detectable amounts of satellite DNA. Alkaline phosphatase digestion of the H1 histones reveals that H1c is the phosphorylated form of H1b and H1e is the phosphorylated form of H1d. Therefore, the under-replication of satellite DNAs is correlated with the decreased phosphorylation of H1 histones. In vitro, D. virilis H1 histones preferentially bind D. virilis DNAs in the progression III greater than II greater than I greater than main band, whereas D. virilis core histones do not preferentially bind any D. virilis DNA. As an extension of these results, we suggest that phosphorylated H1 histones bind D. virilis satellite DNAs in vivo and are involved in the compaction of heterochromatin.